When I was you - Garza, Amber, 1977- (Mira, 2020)
"When Kelly Medina gets a call from her son's pediatrician to confirm her upcoming appointment, it is a case of mistaken identity, but when Kelly happens to bump into the single mother, who shares her name, outside the pediatrician's office their unlikely friendship brings Kelly a renewed sense of purpose that may cost her." --